Implementasi Etika Belajar Kitab Ta'lim Muta'llim dalam Pembentukan Adab Santri: Studi Kasus di STI Pondok Pesantren Islam Darusy Syahadah Boyolali - Muhammad Aidil Akbar; Joko Subando (Lembaga Yasin AlSys, 2026)
The decline in the quality of students’ learning etiquette in the digital era and the limited empirical studies on the implementation of the values of Ta‘līm al-Muta‘allim in pesantren institutions with a love- and deep learning-based curriculum model form the basis for conducting this study. This study aims to describe the implementation of learning ethics in the book Ta‘līm al-Muta‘allim and analyze its contribution to the formation of students’ learning etiquette at the Syu‘bah Ta’shil ‘Ilmy (STI) Unit of Pondok Pesantren Islam Darusy Syahadah, Blagung, Boyolali. This study used a qualitative approach with a case study design. Data were collected through in-depth interviews with 5 ustadz and 10 santri, participatory observation, and documentation study, then analyzed using the Miles, Huberman, and Saldaña interactive model. The results showed that STI Darusy Syahadah implemented the learning ethics of Ta‘līm al-Muta‘allim through three main pathways, namely direct study of the book, internalization of values in daily activities, and the exemplary conduct of ustadz. This implementation contributed to the formation of students’ learning etiquette in three dimensions, namely correct learning intention, ta‘zhim toward teachers, and an ethos of earnest learning. The conclusion of this study affirms that the classical values of Ta‘līm al-Muta‘allim remain relevant and effective in shaping students’ learning etiquette in the contemporary era when implemented systematically and contextually. The implications of this study contribute to strengthening adab-based Islamic education and serve as a practical reference for pesantren in integrating classical learning ethics values with the needs of modern learning.